2016
DOI: 10.1016/j.jaip.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Persistence to Treatment among Patients with Asthma or COPD Receiving AirFluSal Forspiro or Seretide Diskus Salmeterol/Fluticasone Propionate Combination Therapy

Abstract: In this large retrospective pharmacy database analysis, patients using AirFluSal Forspiro were more likely to persist with treatment compared with those using Seretide Diskus as demonstrated by the overall survival experience of the 2 populations (12-month study period). These new data provide a basis for further research to better understand persistence behavior and to develop strategies to address poor persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Persistence is therefore also an important indication of patients’ long-term behavior impacting clinical outcome. Factors associated with poor persistence in patients may include lack of symptoms, confusion around medications, and difficulty in handling the inhaler device 20. Among other factors, level of patient knowledge/education, inhaler convenience and satisfaction, age, adverse effects and medication costs may influence nonadherence in patients with COPD 21…”
Section: Introductionmentioning
confidence: 99%
“…Persistence is therefore also an important indication of patients’ long-term behavior impacting clinical outcome. Factors associated with poor persistence in patients may include lack of symptoms, confusion around medications, and difficulty in handling the inhaler device 20. Among other factors, level of patient knowledge/education, inhaler convenience and satisfaction, age, adverse effects and medication costs may influence nonadherence in patients with COPD 21…”
Section: Introductionmentioning
confidence: 99%
“…Although effective COPD treatments are available, observational studies have shown varying results regarding the association of treatment adherence or persistence with exacerbations and healthcare resource use (HRU) 812. While persistence is defined as the absence of critical gaps in treatment (ie continuation of therapy), adherence is defined as the regular intake of a drug (implementation) 1317. A good understanding of the level of COPD treatment persistence in patients could help optimize disease management and quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…Real-world data provide valuable information on the effectiveness of treatment in a much wider patient population than would be evaluated in a Phase III clinical trial program. Persistence to treatment with fluticasone propionate/salmeterol via the Forspiro device relative to another dry powder inhaler (Seretide ® Diskus ® ; GlaxoSmithKline, Brentford, UK) has already been assessed in a large retrospective analysis of a pharmacy database, which showed greater persistence with the Forspiro device in patients with asthma and chronic obstructive pulmonary disease (COPD) 14. The noninterventional study ASSURE was designed primarily to assess patients’ asthma control and quality of life while using the Forspiro inhaler device in everyday practice, for the treatment of bronchial asthma in line with its licensed indication.…”
Section: Introductionmentioning
confidence: 99%